2011
DOI: 10.1093/nar/gkr020
|View full text |Cite
|
Sign up to set email alerts
|

Uracils at nucleotide position 9–11 are required for the rapid turnover of miR-29 family

Abstract: MicroRNAs are endogenous small RNA molecules that regulate gene expression. Although the biogenesis of microRNAs and their regulation have been thoroughly elucidated, the degradation of microRNAs has not been fully understood. Here by using the pulse–chase approach, we performed the direct measurement of microRNA lifespan. Five representative microRNAs demonstrated a general feature of relatively long lifespan. However, the decay dynamic varies considerably between these individual microRNAs. Mutation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 38 publications
0
39
1
Order By: Relevance
“…Thus, determination of half-lives was hampered by a lack of appropriate model systems. Only in a single recent publication by Zhang et al let-7a displayed a half-live of less than twelve hours 44 in stark contrast to previous publications and our own experiments. This might be due to the use of perfectly complementary miRNA mimics in very high concentrations that might influence the metabolism of miRNAs (e.g., due to a lack of sufficient Ago proteins) and the thermodynamic stability differs from the natural miRNA sequences used in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, determination of half-lives was hampered by a lack of appropriate model systems. Only in a single recent publication by Zhang et al let-7a displayed a half-live of less than twelve hours 44 in stark contrast to previous publications and our own experiments. This might be due to the use of perfectly complementary miRNA mimics in very high concentrations that might influence the metabolism of miRNAs (e.g., due to a lack of sufficient Ago proteins) and the thermodynamic stability differs from the natural miRNA sequences used in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agreement with our observations from in situ hybridization (Roshan et al 2012) and reports from other groups in HeLa cells (Hwang et al 2007) and in renal medulla of rats. miR-29a transcripts have also been shown to be more stable than miR-29b transcripts (Zhang et al 2011). In vivo, LNA29 effectively down-regulated miR-29a and miR29b in different parts of the brain (Fig.…”
Section: Mir-29 Regulates Neuronal Apoptosis Through Vdac1mentioning
confidence: 91%
“…The miR-29 family consists of miR-29a, miR-29b-1, miR-29b-2, and miR-29c, of which miR-29c has very low expression, perhaps due to a high turnover rate (Zhang et al 2011;Kriegel et al 2012). The mature sequences of these miRNAs are highly conserved in human, mouse, and rat.…”
Section: Introductionmentioning
confidence: 99%
“…Others demonstrated that the differences between miR-29a and miR-29c result in the relatively quicker decay of miR-29c (ref. 24 ).…”
Section: Regulation Of Mir-29 Expressionmentioning
confidence: 99%